A guide to oral history and the law - Neuenschwander, John A. (Oxford University Press, 2014)
A Guide to Oral History and the Law is the definitive resource for all oral history practitioners. In clear, accessible language it thoroughly explains all of the major legal issues including legal release agreements, the protection of restricted interviews, the privacy torts (including defamation), copyright, the impact of the Internet, and the role of Institutional Review Boards (IRBs). The author accomplishes this by examining the most relevant court cases and citing examples of policies and procedures that oral history programs have used to avoid legal difficulties. Neuenschwander's central focus throughout the book is on prevention rather than litigation. He underscores this approach by strongly emphasizing how close adherence to the Oral History Association's Principles and Best Practices provides the best foundation for developing sound legal policies. The book also provides more than a dozen sample legal release agreements that are applicable to a wide variety of situations. This volume is an essential one for all oral historians regardless of their interviewing focus.